Perkawinan Usia Muda dan Pengaruhnya terhadap Tingkat Perceraian di Desa Sei Mencirim Kabupaten Deli Serdang: Early Marriage and Its Impact on the Divorce Rate in Sei Mencirim Village, Deli Serdang Regency - Nindy Aulia Pratiwi; Ramadhan Putra Gayo (Information Technology and Science (ITScience), 2026)
Early marriage is still prevalent in Sei Mencirim Village and is influenced by various social, economic, and cultural conditions, as well as legal enforcement. This study aims to analyze the factors driving early marriage, its implications for divorce vulnerability, and the implementation of Law Number 16 of 2019. The study used an empirical juridical method with a qualitative approach. Primary data were obtained through interviews with the Head of the Sunggal District Office of Religious Affairs (KUA), traditional leaders, and purposively selected parents. Secondary data were sourced from KUA documentation, laws and regulations, and related literature. Data were analyzed qualitatively and tested through source triangulation. Economic limitations, low education, cultural pressures, premarital pregnancy, and suboptimal legal prevention influence early marriage. KUA documentation shows 36 marriages involving prospective brides and grooms under the age of 19 during the period 2022–2024. These factors are interrelated and increase the vulnerability of household conflict due to the psychological, social, and economic unpreparedness of couples. The implementation of the minimum marriage age has not been fully supported by legal education, data collection, and inter-institutional coordination. Early marriage does not automatically lead to divorce, but it can increase vulnerability. Prevention requires increased access to education, economic empowerment, reproductive health education, strengthening the role of families, and coordination between village governments, the Religious Affairs Office (KUA), schools, community health centers (Puskesmas), and community leaders.